JARAK ROTOR YANG OPTIMAL TERHADAP RIPPLE PLATE PADA MESIN RIPPLE MILL UNTUK EFISIENSI HASIL PEMECAH BIJI KELAPA SAWIT CB MODIPALM KAPASITAS 8 TON/JAM - Harianto, Agus; Aspiyansyah, Aspiyansyah; Faot , Ecy Yedija (Jurnal Rekayasa Mesin, 2024)
A ripple mill machine is one of the crucial pieces of equipment in the palm oil processing industry to separate oil palm kernels into fruit kernels and shells. One of the key components in this machine is the rotor and ripple plate, which play a role in the process of breaking seeds. This study aims to determine the optimal distance between the rotor and ripple plate on the ripple mill machine. The test was conducted using a CB Modipalm-type ripple mill machine. The parameter observed was the cracking efficiency of oil palm kernels, which was measured based on the percentage of cracked seeds, whole seeds, and crushed kernels. The results showed that the optimal distance between the rotor and ripple plate was 5 mm, with an efficiency value of 96.62%.